Pemberdayaan Ibu-Ibu PKK Kelurahan Sawah Lebar Dengan Memanfaatkan Limbah Rumah Tangga - Gustini, Gustini; Dinsan, Dinsan; Ermansyah, Ermansyah (Universitas Dehasen Bengkulu, 2021)
The empowerment program of PKK women in Sawah Lebar Urban Village through household waste utilization is a strategic effort in improving the welfare of local communities while promoting environmentally friendly practices. This study aims to evaluate the effectiveness and impact of this empowerment program on PKK women's participation, household waste management, and the resulting economic benefits. The research method used involved surveys, interviews, and observations to collect data before and after the program implementation. The results showed that the empowerment program for PKK women in Sawah Lebar Village successfully increased their awareness and participation in household waste management. Through training and guidance, the women learned how to identify, sort and utilize household waste creatively, such as by recycling or processing it into products with economic value. Positive impacts are also seen in the increase of family income through the sale of recycled or processed household waste products. In conclusion, the empowerment program for PKK women by utilizing household waste in Sawah Lebar Urban Village has a positive impact in increasing their participation, skills and economic income. The program not only provides economic benefits, but also supports waste mitigation efforts and the promotion of sustainable lifestyles at the local level. Continued support and monitoring is required to ensure the sustainability and future development of this program.